Analisis Keputusan Ibu Memilih Penolong Persalinan Di Wilayah Puskesmas Kabila Bone - Parenden, Relik Diana (JIKMU, 2015)
Abstrak Indikator tercapainya sasaran program MDG’s tahun 2015 adalah presentase ibu bersalin yang ditolong oleh nakes sebesar 90%. Hasil Riset Kesehatan Dasar, 2013 mencatat bahwa persalinan tenaga kesehatan dengan kualifikasi terendah mencapai 80,9%, dan capaian persalinan oleh nakes di Kab. Bone Bolango mencapai 77,2%. Data Puskesmas Kabila Bone tahun 2013 persalinan yang di tolong oleh tenaga kesehatan sebanyak 172 (80,2 %) dari 2013 ibu bersalin, dengan demikian sekitar 9,8% persalinan masih ditolong oleh dukun bayi (hulango) dari 90 % target MDG’s. Jumlah kematian ibu di Puskesmas Kabila Bone tahun 2013 sebanyak 2 kasus, salah satu penyebab kematian di tangani oleh dukun bayi. Jenis penelitian yang digunakan adalah penelitian kualitatif, untuk mendapatkan informasi yang lebih mendalam tentang bagaimana menganalisis keputusan ibu memilih penolong persalinan di wilayah kerja Puskesmas Kabila Bone. Data dikumpulkan melalui wawancara mendalam,dan melakukan reduksi data, penyajian dalam bentuk narasi dan keabsahan data dengan trianggulasi sumber dan trianggulasi metode. Data dianalisis dengan menggunakan analisis isi yaitu membandingkan hasil penelitian dengan teori-teori yang ada dikepustakaan. Informan dalam penelitian ini sebanyak 10 informan. Hasil penelitian menunjukkan keputusan ibu memilih penolong persalinan sangat berkaitan dengan, pengetahuan, sikap, akses pelayanan, dukungan suami dan keluarga serta tradisi/budaya setempat Kata kunci: Penolong Persalinan, Keputusan memilih, Dukun Bayi, Bidan. . Abstract One of the indicators of MDGs that has to be reached by 2015 is that 90% of baby deliveries attended by the skilled health personnels. The result on the Basic Health Survey (RISKESDAS) conducted in 2013 shown that the deliveries attended by least qualified health personnel were 80.9% and that the deliveries attended by skilled health personnel in the level of Bone Bolango district was 77.2%. The data in the Health Center of Kabila Bone in 2013, shown that there were 172 (80.2%) births attended by skilled health personnel. Thus, it only indicated that out of the 90% birth attended by skilled health personnel as mentioned in MDGs indicators, there were still 9.8% of the birth were attended by the traditional birth attendants (or in local language called hulango). The number of mother mortality in Kabila Bone Health Center in 2013 were 2 cases, one of the causes of the death was the delivery process was only attended by the traditional midwives. This research used qualitative method to gain the in-depth information on how to analyse mother’s decision to choose for birth attendants in the area of Kabila Bone Health Centre. The data in this research are collected through in-depth interview, and the data are reduced and presented in narration order. To ensure that the data presented are the valid data, the data are further analysed through the data source triangulation and the method triangulation. The data are analysed by using content analysis, which is comparing the result from the research with the theories in the literature. There were 10 informants in this research. Results of this study shows that the decision for birth attendants are closely related to knowledge, attitude, access to health centre, support from husband and family, and the local customs and tradition Keyword: Birth Attendants, Decision to choose, Traditional Midwives, and trained Midwives.